Aptis Distal Radioulnar Joint Arthroplasty: A Multicenter Evaluation of Functional Outcomes, Complications, and Patient Satisfaction - Stougie, Shirley D.; Boekel, Leonieke C. van; Beumer, Annechien; Hoogvliet, Peter; Strackee, Simon D.; Coert, J. Henk (Journal of Wrist Surgery, 2023)
Background The Aptis distal radioulnar joint (DRUJ) implant has been commonly used to replace the DRUJ and restore wrist function in patients with a severely destroyed DRUJ.Objective Promising results have been described in the literature. However, the clinical results in a multicenter setting are sparse and variable. This study evaluates the short- to midterm clinical results of 53 patients with a (mean) follow-up of 51 months.Patients and Methods Fifty-three patients (59 implants) treated between 2011 and 2020 in three different institutions were retrospectively identified in a prospectively collected database. The main indication for Aptis DRUJ arthroplasty was a destroyed DRUJ and gross distal radioulnar instability and isolated DRUJ osteoarthritis. Functional outcome, complications, and patient satisfaction were evaluated. Patients completed the Patient-Rated Wrist Evaluation (PRWE) questionnaire and an additional questionnaire about patient satisfaction and return to hobby/work.Results Implant survival was 92%, the surgical follow-up showed many complications (64,4%), and revision surgery was needed frequently (40.7%). In 13 cases, the follow-up was longer than 5 years. Three reimplantations had to be performed and two implants were permanently explanted. In spite of this all, wrist and forearm motion as well as pain reduction was adequate and patient satisfaction was reasonable (72.2%).Conclusion The Aptis DRUJ arthroplasty is a viable option that can provide adequate wrist and forearm function after secure patient selection and surgical placement of the implant in the wrist with a good bone stock of the radius. The complication rate was found to be high, yet patient satisfaction was reasonable. In the case of secondary surgery, additional surgery seems to be needed. For primary surgery, the implant seems to be successful without complications. Different complications have been described, but further analysis is warranted to find the causes of complications and to objectify the performance of the Aptis DRUJ implant.Level of Evidence IV.
Keywords: distal radioulnar joint; arthroplasty; functional outcomes; complications; joint replacement